2019
DOI: 10.1002/jcsm.12412
|View full text |Cite
|
Sign up to set email alerts
|

4E‐BP1 and 4E‐BP2 double knockout mice are protected from aging‐associated sarcopenia

Abstract: Background Sarcopenia is the loss of muscle mass/function that occurs during the aging process. The links between mechanistic target of rapamycin (mTOR) activity and muscle development are largely documented, but the role of its downstream targets in the development of sarcopenia is poorly understood. Eukaryotic initiation factor 4E‐binding proteins (4E‐BPs) are targets of mTOR that repress mRNA translation initiation and are involved in the control of several physiological processes. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Interfering with other major outputs of mTORC1 activity, such as autophagy and cap-dependent translation, does not seem to affect cyst formation. Autophagy mutants and 4E-BP1/4E-BP2-deficient mice do not recapitulate a polycystic kidney phenotype 52,53 . We can speculate that the S6K1dependent phosphoproteome orchestrates a pleiotropic response required for the intense tissue remodeling in polycystic kidneys.…”
Section: Discussionmentioning
confidence: 98%
“…Interfering with other major outputs of mTORC1 activity, such as autophagy and cap-dependent translation, does not seem to affect cyst formation. Autophagy mutants and 4E-BP1/4E-BP2-deficient mice do not recapitulate a polycystic kidney phenotype 52,53 . We can speculate that the S6K1dependent phosphoproteome orchestrates a pleiotropic response required for the intense tissue remodeling in polycystic kidneys.…”
Section: Discussionmentioning
confidence: 98%
“…[ 37 ] Previous studies also reported that mice knocking out 4EBP1 showed a reduction in adipose tissue but mice knocking out 4EBP1 and 4EBP2 reversed this phenomenon. [ 38,39 ] These results indicated that the tissue‐specific effect mediated by different 4E‐BP family members in the regulation of metabolic homeostasis might be masked in whole‐body knockout mice. Effect of 4EBP varies from mice at different age.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the Eif4ebp1 −/− and Eif4ebp2 −/− double knockdown (4EBP1/2 DKO) mice have been used to study the regulation of skeletal muscle protein synthesis. The depletion of 4E-BPs is associated with perturbed energy metabolism in skeletal muscles, and it has also been suggested that 4E-BP can be a target of sarcopenia intervention [ 158 ]. The use of growth hormone receptor knockout (GHR −/− ) and bovine GH mice provided evidence that the insulin-like growth factor 1 (IGF-1) signaling pathway predominantly regulates myostatin, which is a negative regulator of myogenesis [ 159 ].…”
Section: Models For Studying Sarcopeniamentioning
confidence: 99%